Comportamiento de la cartera del impuesto vehicular en el departamento del Chocó (2018 – 2022). Estrategias de recuperación de cartera - Guevara Córdoba, Gina Marcela; Lemus Garrido, Luis Eduardo (Universidad Antonio Nariño, 2023)
The purpose of this article is to develop an analysis of the behavior of the motor vehicle tax portfolio in the department of Chocó valid for 2018 - 2022, to consolidate portfolio recovery strategies.